TRAIN STUDENTS’ CRITICAL THINKING SKILL THROUGH THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION (GI) ON MATTER OF REACTION RATE INSMA NEGERI 1 MANYAR - KHASANAH, NIKMATUL; AZIZAH, UTIYA (Universitas Negeri Surabaya, 2018)
This study aims to determine the implementation of learning and students' critical thinking skills after the implementation of cooperative learning model type Group Investigation on matter of reaction rate. This research type is Pre Experiment (pre experimental design) and research design used is One-Group Pretest-Postest Design. Target of this research is student of class XI MIPA 6 SMA Negeri 1 Manyar. The instrumentsused are an observation sheet of cooperative learningmodeltype Group Investigation and sheet of pretest and postest of critical thinking skill. The results showed that (1) The implementation of cooperative learning model type Group Investigationis in good and very good category with percentage in every phase is:in phase 1 was 87.5%; phase 2 was 95.84%; phase 3 which contains stage 1 and stage 2 of the Group Investigation was 87.5%; Phase 4 which contains stage 3, stage4, and stage5 of the Group Investigation was 95.84%; phase 5 which contains stage 6 of Group Investigation was100%; (2) Students’ critical thinking skill in terms of N-gain shows that 85% of students get high N-gain category and 15% of students get N-gain in moderate category.